Stability of Four Commercial Phytase Products under Increasing Conditioning Temperature - J. A. De Jong; J. C. Woodworth; J. M. DeRouchey; M. D. Tokach; R. D. Goodband; S. S. Dritz; C. K. Jones; C. R. Stark (Kansas Agricultural Experiment Station Research Reports, 2015)
A study was conducted to determine the stability of four commercial phytase products exposed to increasing conditioning temperatures. The four commercial products used were: Quantum Blue G (AB Vista, Plantation, FL); Ronozyme Hi Phos GT (DSM Nutritional Products, Parsippany, NJ); Axtra Phy TPT (Dupont, Wilmington, DE); and Microtech 5000 Plus (Guangdong Vtr Bio-Tech Co., Ltd., Guangdong, China). The phytase products were mixed as part of corn-soybean meal-based swine diet at a concentration recommended to provide a 0.12% aP release. All four diets were analyzed for phytase activity to establish baseline phytase activity for each product. Diets were then conditioned at four temperatures (149, 167, 185, and 203˚F). The entire process was repeated on four consecutive days to create four replicates. Samples were taken while feed exited the conditioner and before entering the pellet die. Phytase stability was expressed as the residual phytase activity (% of baseline) at each conditioning temperature. No product × temperature interactions were observed for actual conditioning temperature, conditioner throughput, or residual phytase activity. As the target temperature increased the conditioning temperature increased (linear; P<0.001) and conditioner throughput decreased (linear; P<0.001). No evidence was observed for effects of phytase product on conditioning temperature or conditioner throughput. As target temperature increased, phytase activity decreased (linear; P<0.001). Residual phytase activity decreased 1.07% for every 1˚F increase in conditioning temperature between the target temperatures of 149 to 203˚F. The product main effect was significant (P<0.001). The Microtech 5000 Plus had decreased (P<0.05) phytase activity when compared to all other products. There was no evidence for residual phytase differences between the Quantum Blue G, Ronozyme Hi Phos GT, or Axtra Phy TPT products. In the current experiment, target conditioning temperatures had a significant effect on phytase stability regardless of product, resulting in linear decreases in residual phytase activity as temperature was increased. However, Microtech 5000 Plus had decreased residual phytase activity (% of initial) when compared to all other products.
Keywords: conditioning temperature; pelleting; phytase stability